Physicochemical and functional properties of modified potato starch from different altitudes: a study of the medians cultivar - Ira Endah Rohima; Mohamad Djali; Yana Cahyana; Jajang Sauman Hamdani; Mohd Nizam Lani; Rini Triani (Discover Food)
Abstract Potato (Solanum tuberosum L.) cultivation faces significant challenges: highland cultivation leads to soil erosion and fertility degradation, while medium-land cultivation is constrained by suboptimal temperature and humidity conditions. Processing potatoes into starch improves shelf life and economic value, however, native potato starch has limited food applications due to heat sensitivity, high viscosity, and its propensity for retrogradation and syneresis. This study investigated the effects of cultivation altitude and modification methods on the physicochemical and functional properties of potato starch from ‘Medians’ cultivar, comparing samples from medium-land (765 m above sea level) and highland (1312 m above sea level) locations. Starch modifications included Heat Moisture Treatment (HMT), crosslinking with Monosodium Phosphate (MSP), and a combined treatment (CLM-HMT). A factorial randomized complete block design was employed to analyze physicochemical characteristics, functional properties, and pasting behavior, with statistical significance determined using two-way ANOVA and Duncan’s Multiple Range Test (p < 0.05). Results revealed significant effects of cultivation altitude, modification method, and their interaction on starch properties. Highland-grown modified starch exhibited superior characteristics in color properties and thermal stability. Modification methods improved starch thermal stability and minimized retrogradation, with the combined CLM-HMT treatment yielding optimal results. This study provides valuable insights into optimizing potato starch production and modification techniques, contributing to sustainable agriculture and broadening its applications in the food industry.